Extracellular vesicle GABA responds to cadmium stress, and GAD overexpression alleviates cadmium damage in duckweed - Sun, Zhanpeng; Qu, Ziyang; He, Yuman; Han, Yujie; Xing, Yun; Liu, Sizheng; Hu, Yi; Jiang, Yumeng; Yu, Yiqi; Liu, Yuanyuan; Sun, Weibo; Yang, Lin (Frontiers in Plant Science, 2025)
IntroductionCadmium (Cd) pollution lead to ecological problems and cause severe damages to plants. Investigating the signal response to Cd is crucial for improving Cd resistance during phytoremediation. While γ-aminobutyric acid (GABA) is known to accumulate rapidly under environmental stress, the real-time dynamics of GABA signaling and its mechanistic link to stress adaptation remain poorly understood.MethodsIn this study, a sensitive GABA biosensor, iGABASnFR, was introduced into plants for the first time to monitor GABA signaling. Additionally, glutamate decarboxylase (GAD), a key enzyme catalyzing the conversion of glutamate (Glu) to GABA, was overexpressed in duckweed. The responses of GABA in extracellular vesicles (EVs) under Cd stress were analyzed using iGABASnFR transgenic duckweed. Cd accumulation, photosynthesis, and antioxidant activity were evaluated in GAD-overexpressing duckweed.Results(1) GABA in extracellular vesicles of duckweed exhibited a dynamic response to Cd stress, as visualized by iGABASnFR transgenic duckweed. GABA content in EVs was significantly enhanced under Cd treatment. (2) GAD-overexpressing duckweed demonstrated improved photosynthetic efficiency and enhanced antioxidant capacity during Cd stress. (3) Cd accumulation was significantly increased in GAD transgenic duckweed, as evidenced by Cd2+ flux measurements, total Cd content, and Cd staining in protoplasts using FlowSight imaging.DiscussionThis study provides novel insights into the role of GABA in extracellular vesicles during Cd stress and establishes a direct link between GABA signal and Cd stress adaptation. The findings demonstrate that GAD overexpression enhances Cd resistance and accumulation in duckweed, offering a potential strategy for improving phytoremediation efficiency. This work advances our understanding of GABA signaling dynamics and its application in Cd stress.